DATA MINING PENGELOMPOKAN BARANG MAKANAN RINGAN/ SNACK MENGGUNAKAN METODE CLUSTERING - Riska Kurniawati; Magdalena Simanjuntak; Husnul Khair (Jurnal Abdi Ilmu, 2021)
Liquid snacks of one of the areas of business are growing rapidly in Indonesia, with the increasing number of population. Nowadays many snacks factories that produce products with various vasiasi so as to make skating have a lot that when want to buy. In connection with this it is required that the breadth of goods grouping system is in demand. To make the slide can determine there according to the wishes. This designed system uses Clustering method. In Clustering method The data segmentation method is very useful for predicting and analyzing literature, and from good Clustering results will result in a high level of similarity.